THE JFK ASSASSINATION DEBATES : Lone Gunman versus Conspiracy - Kurtz, Michael L., 1941- (Book collections on Project MUSE., 2006)
Summarizes--and critiques--more than four decades of debates over the controversial murder of President John F. Kennedy. Dissects the two major paradigms--lone gunman versus conspiracy--giving each argument its due, but also pointing out the limitations of each before ultimately siding with some of the more sober-minded conspiracy theorists.